Rancang Bangun Sistem Penjualan Online Berbasis Android Menggunakan Metode UML - Sadiah, Ashifa Halimatus; Voutama, Apriade (INFORMAL: Informatics Journal, 2024)
The rapid development of online shopping in Indonesia has encouraged business actors, including NICESO Store, to develop Android-based online sales applications that facilitate the transaction process for customers and simplify data management through e-commerce. To that end, NICESO developed a sales application that makes it easier for customers to search for and buy products without having to come to the store. This study itself uses the Quality Function Deployment (QFD) method to analyze consumer needs, as well as UML diagrams such as Use Case, Activity, Sequence, and Class Diagram to design the application. As a result, this application simplifies the process of ordering, paying, and tracking orders online with a simple and easy-to-use display. In conclusion, this sales application expands NICESO's market, simplifies online transactions, and helps stores in sales reporting.